2009
DOI: 10.1016/j.proche.2009.07.334
|View full text |Cite
|
Sign up to set email alerts
|

Drug Delivery Micropump with Built-In Monitoring

Abstract: We report on the fabrication of the first MEMS micropump including an integrated pressure sensor. The signal of this sensor allows direct insight into the pump's operating dynamics and enables real-time self-monitoring. We demonstrate the changes in the sensor signal under different pumping conditions, including the presence of air in the pumping chamber and a downstream occlusions. Deviations from normal operating conditions create clear and characteristic deviations from the normal signal. These deviations w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…Because of the rigidity of the system (silica chip, membrane), the JP showed a quick response to a full occlusion (after 3 or 4 strokes) compared to other pumps made of more readily deformable materials (plunger, plastic reservoir, catheter). 18 Previous studies on cessation of rapid delivery of insulin analogues showed that glycemic changes began to occur 1 hour after cessation and were more consistent after 2 or 3 hours. [19][20][21][22] In the case of a 2-hour overnight insulin cessation, glucose levels at the end of the interruption period rose by 16 ± 34 mg/dL at 2 hours and by 63 ± 57 mg/ dL at 4 hours.…”
Section: Discussionmentioning
confidence: 97%
“…Because of the rigidity of the system (silica chip, membrane), the JP showed a quick response to a full occlusion (after 3 or 4 strokes) compared to other pumps made of more readily deformable materials (plunger, plastic reservoir, catheter). 18 Previous studies on cessation of rapid delivery of insulin analogues showed that glycemic changes began to occur 1 hour after cessation and were more consistent after 2 or 3 hours. [19][20][21][22] In the case of a 2-hour overnight insulin cessation, glucose levels at the end of the interruption period rose by 16 ± 34 mg/dL at 2 hours and by 63 ± 57 mg/ dL at 4 hours.…”
Section: Discussionmentioning
confidence: 97%
“…The device is driven by a battery-powered piezoelectric actuator that delivers insulin from a disposable reservoir worn as a patch on the skin for seven days. [ 96 ] The system can be wirelessly programmed and monitored using a cell phone. [ 97 ] While this system is in fi nal stages of development in Europe, Debiotech is also in the process of further miniaturizing the device so that it can be completely implanted inside the body.…”
Section: Jewelpumpmentioning
confidence: 99%
“…Various methods have been explored for pumping at the microscale including nonmechanical mechanisms, such as electrohydrodynamic, electroosmotic, ultrasounic and thermo-capillary mechanisms [39], as well as mechanical mechanisms such as electrostatic [40-44], piezo-electric [45-55], electrochemical [56-64], thermal [65-69], shape memory alloy [70,71], bimetallic and electromagnetic mechanisms. These and other drug-delivery mechanisms are explored in more depth in several engineering-focused reviews [72-75].…”
Section: Drug-infusion Micropumpsmentioning
confidence: 99%
“…The JewelPump is designed to be worn on the skin as a patch and comes with a 4.5 ml reservoir [104]. The piezoelectric pump contains a pair of mechanical oneway (check) valves to control flow direction and also a double limiter feature that provides accurate and repeatable control of fluid packets delivered by the pump with each reciprocation cycle [45,47]. An active microport system concept was proposed by an academic group using a piezoelectric pump for patient-specific, continuous release of antiangiogenic drugs targeting metronomic and chronotherapies against cancer [54,55].…”
Section: Drug-infusion Micropumpsmentioning
confidence: 99%